Biogênese do vacúolo de Leishmania: papel da subunidade ATP6V0d2 na homeostase de colesterol - Pessoa, Carina Carraro [UNIFESP] (2019)
Vacuolar H+-ATPases (v-ATPases) are membrane-associated ATP-dependent multimeric enzymes responsible for pumping protons from the cytosol into the lumen of intracellular organelles, thus controlling the acidification of lysosomes, endosomes and other intracellular vesicles. It exhibit two functional domains, the V1 (cytosolic, composed of 8 subunits) and V0 (membranous, composed of 6 subunits). In addition to organelle acidification, v-ATPases are alternatively implicated in membrane fusion and anti-inflammatory functions controlled by a variant subunit, d2, of the V0 domain (ATP6V0d2). Leishmania spp. are parasites that cause cutaneous or visceral leishmaniasis in humans and other animals and are a major health problem in poor and developing countries. They are dimorphic parasites found extracellularly in the midgut of insect vectors as flagellated and elongated promastigotes and intracellularly in mammalian host macrophages as rounded amastigotes. Species such as Leishmania (Leishmania) amazonensis, L. mexicana and L. pifanoi are known to multiply in large and fusogenic vacuoles parasitoforos (VP), inducing the positive regulation of ATP6V0d2. In comparison to other Leishmania species, they also exhibit, at least in vitro, remarkable resistance to mechanisms of parasite elimination mediated by interferon-gamma (IFN-γ) and lipopolysaccharide (LPS) within macrophages or by direct treatment with species reactive oxygen species (ROS). However, a causal relationship between the development of large VPs and parasite resistance in inflammatory macrophages remains unclear, especially in vivo. Therefore, we evaluated the role of ATP6V0d2 in the biogenesis of pathogen-containing vacuoles using macrophages silenced to ATP6V0d2 infected with the protozoan parasite L. amazonensis. ATP6V0d2 knock-down decreased the cholesterol levels of the macrophages and inhibited the increase of the VP without interfering in the multiplication of the parasite. However, the parasites required ATP6V0d2 to resist the influx of oxidized low-density lipoprotein cholesterol (ox-LDL), which restored the increase of VP in silenced macrophages by replacing the cholesterol of the macrophages. Thus, we disclose the subversion of parasite-mediated V-ATPase function of the host cell relative to cholesterol retention, which is required to establish an inflammatory resistant intracellular parasite niche.